Presence of Trifolium repens Promotes Complementarity of Water Use and N Facilitation in Diverse Grass Mixtures - Hernandez, Pauline; Picon-Cochard, Catherine (Frontiers in Plant Science, 2016)
Legume species promote productivity and increase the digestibility of herbage in grasslands. Considerable experimental data also indicate that communities with legumes produce more above-ground biomass than is expected from monocultures. While it has been attributed to N facilitation, evidence to identify the mechanisms involved is still lacking and the role of complementarity in soil water acquisition by vertical root differentiation remains unclear. We used a 20-month mesocosm experiment to investigate the effects of species richness (single species, two- and five-species mixtures) and functional diversity (presence of the legume Trifolium repens) on a set of traits related to light, N and water use and measured at community level. We found a positive effect of Trifolium presence and abundance on biomass production and complementarity effects in the two-species mixtures from the second year. In addition the community traits related to water and N acquisition and use (leaf area, N, water-use efficiency and deep root growth) were higher in the presence of Trifolium. With a multiple regression approach, we showed that the traits related to water acquisition and use were with N the main determinants of biomass production and complementarity effects in diverse mixtures. At shallow soil layers, lower root mass of Trifolium and higher soil moisture should increase soil water availability for the associated grass species. Conversely at deep soil layer, higher root growth and lower soil moisture mirror soil resource use increase of mixtures. Altogether, these results highlight N facilitation but almost soil vertical differentiation and thus complementarity for water acquisition and use in mixtures with Trifolium. Contrary to grass-Trifolium mixtures, no significant over-yielding was measured for grass mixtures even those having complementary traits (short and shallow vs tall and deep). Thus, vertical complementarity for soil resources uptake in mixtures was not only dependant on the inherent root system architecture but also on root plasticity. We also observed a time-dependence for positive complementarity effects due to the slow development of Trifolium in mixtures, possibly induced by competition with grasses. Overall, our data underlined that soil water resource was an important driver of over-yielding and complementarity effects in Trifolium-grass mixtures.